Panel Data Analysis of the Impact of Economic Freedom as Well as Economic Conditions, The Quality of Life, and Public Education Spending on U.S. Undocumented Immigrant Settlement Patterns - Cebula, Richard J (Quarterly Journal of Econometrics Research, 2016)
This study seeks to identify key factors influencing the geographic settlement pattern of undocumented immigrants in the U.S., with a particular emphasis on the impact of economic freedom, and to extend the OLS findings in previous related studies. Indeed, this study adds to the literature in several ways. First, it provides current insights into the link between the settlement patterns of undocumented immigrants in the U.S. and economic freedom. Second, the study adopts a panel data-set and provides estimates using cross-section fixed-effects. Third, this study also endeavors to provide further insights into the impacts on the settlement patterns of undocumented immigrants of non-economic-freedom economic conditions, as well as the quality of life and spending on primary and secondary public education. The various state fixed-effects estimates provided in the present study yield several conclusions. In particular, according to these estimations, the settlement pattern of undocumented immigrants in the U.S is inversely a function of colder climates, higher crime rates, higher population density, and a higher cost of living. In addition, the interstate distribution of undocumented immigrants to the U.S. is positively a function of the annual per pupil outlays on public primary and secondary education; it is also positively a function of the degree of economic freedom, the principal focus of this study.